2021
DOI: 10.35542/osf.io/ye6uw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Reality in Teacher Education From 2010 to 2020: A Review of Program Implementation, Intended Outcomes, and Effectiveness Measures

Abstract: Virtual reality (VR) is a technology that recreates realistic scenarios in a controllable virtual environment. VR has been widely adopted in professional training of situational, adaptive, and complex skills within various occupations, yet the field of teacher education has only just started to utilize this technology in the recent decade. In order to advance the application of VR in teacher education, the current review presents a synopsis of state-of-the-art literature from 2010 to 2020. We conducted a revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(56 reference statements)
1
8
0
1
Order By: Relevance
“…A simulated classroom in VR allows teachers to experience and interact with classroom events firsthand instead of watching videos that provide at best a “secondhand experience” (Miller & Zhou, 2007, p. 322). As fully immersive VR headsets have become more widely available in recent years (Lamb & Etopio, 2020), researchers and teacher educators are increasingly utilizing this technology for training purposes (for a review, see Huang, Richter, Kleickmann, & Richter, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simulated classroom in VR allows teachers to experience and interact with classroom events firsthand instead of watching videos that provide at best a “secondhand experience” (Miller & Zhou, 2007, p. 322). As fully immersive VR headsets have become more widely available in recent years (Lamb & Etopio, 2020), researchers and teacher educators are increasingly utilizing this technology for training purposes (for a review, see Huang, Richter, Kleickmann, & Richter, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its capacity to depict an authentic and interactive environment that closely resembles actual scenarios, VR has been widely employed in the training of professionals who must operate in dynamic and complex situations (Howard et al, 2021), such as pilots (Abich et al, 2021) and surgeons (Mao et al, 2021). According to a recent review covering 2010 to 2020 (Huang, Richter, Kleickmann, & Richter, 2021), VR technology has also been used for teacher training in areas including noticing and reacting to misbehaviours (eg, Chen, 2022), subject‐specific pedagogy (Ely et al, 2018) and communicative skills (eg, Spencer et al, 2019) among other competencies (eg, Artun et al, 2020; Stavroulia & Lanitis, 2020). These studies consistently reported positive results regarding the intended outcomes, demonstrating the potential merits of VR in teacher education.…”
Section: Introductionmentioning
confidence: 99%
“…Second, regarding VR applications in teacher education, several studies conducted in‐depth reviews of this topic from different or even overlapping perspectives (e.g., Billingsley et al, 2019; Huang et al, 2023a; McGarr, 2020). For instance, Billingsley et al (2019) examined eight studies using immersive VR in PST training programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that these types of technologies can enrich and improve the learning of future teachers, but research in this area is still greatly lacking. Huang et al (2023a) reviewed 46 studies dedicated to the application of VR in teacher education published from 2010 to 2020. This review study focused on investigating the details of program implementation (e.g., VR system and simulated situations), intended outcomes (e.g., factual/conceptual or procedural knowledge), and measures used to evaluate the effectiveness of programs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation